Influence of Security and Ease of Use on Repurchase Intention on Virtual Hotel Operator (VHO) Websites - Mutiara Aziza Ramadhani (MINOVa Ditria Jaya, 2025)
The advancement of digital technology has significantly driven the growth of the hospitality industry, one of which is the emergence of Virtual Hotel Operators (VHO), which serve as intermediaries between independent hotels and online booking platforms. This study examines how security and ease of use influence repurchase intentions on VHO websites. Quantitative data were collected from 200 Gen Z individuals who had previously booked hotels through VHO websites and analyzed using SEM-Lisrel 8.80. The results show that both security and ease of use significantly affect repurchase intentions. These findings are particularly relevant for Generation Z, as digital-native consumers with high expectations regarding security and ease of use in their digital experiences. If VHO platforms meet these expectations, they are likely to encourage repurchase intentions. Managerial implications include enhancing security systems through encryption and routine security audits, as well as optimizing ease of use with intuitive interface designs and more personalized services. These strategies are expected to improve customer retention and strengthen VHO’s position in the increasingly competitive digital hospitality industry.